Evolving trends and burden of iron deficiency among children, 1990–2019: a systematic analysis for the global burden of disease study 2019 - Long, Dan; Mao, Chenhan; Liu, Yaxuan; Zhou, Tao; Xu, Yin; Zhu, Ying (Frontiers in Nutrition, 2023)
We aimed to provide a timely, comprehensive, and reliable assessment of the burden of iron deficiency (ID) in children between 1990 and 2019 at the global, regional, and national levels to inform policymakers in developing locally appropriate health policies.Data related to ID among children younger than 15 years old were analyzed by sex, age, year, socio-demographic index (SDI), and location according to the Global Burden of Disease Study 2019 (GBD 2019). Age-standardized rates were used to compare the burden between different regions and countries. Furthermore, the Joinpoint regression model was used to assess temporal trends from 1990 to 2019.In 2019, the number of prevalent cases and disability-adjusted life years (DALYs) for ID in children were 391,491,699 and 13,620,231, respectively. The global age-standardized prevalence and DALY rates for childhood ID in 2019 were 20,146.35 (95% confidence interval: 19,407.85 to 20,888.54) and 698.90 (466.54 to 1015.31) per 100,000, respectively. Over the past 30 years, the global prevalence of ID among children has been highest in low-SDI regions, particularly in Western